Specific Sex-Drug Combinations Contribute to the Majority of Recent HIV Seroconversions Among MSM in the MACS - Ostrow, David G. (2009)
BACKGROUND: New HIV infections are being observed among men who have sex with men. Understanding the fusion of risky sexual behaviors, stimulant and erectile dysfunction drug use with HIV seroconversion may provide direction for focused intervention. METHODS: During the follow-up period (1998–2008) we identified 57 HIV seroconverters among 1,667 initially HIV-seronegative men. Time to seroconversion was modeled using Cox proportional hazards regression analysis for 7 combinations of sex-drugs (inhaled nitrites or “poppers”, stimulants, and EDDs) used at the current or previous semi-annual visit, adjusting for other risk factors including sexual behavior, alcohol and other drugs used, and depression. Model-based adjusted attributable risks were then calculated. RESULTS: The risk of seroconversion increased linearly with the number of unprotected receptive anal sex partners (URASP), with hazard ratios (HR) ranging from 1.73 (95% confidence interval [CI]: 0.75, 4.01) for 1 partner, to 4.23 (95% CI: 1.76, 10.17) for 2–4 partners to 14.21 (95% CI: 6.27, 32.20) for 5+ partners, independent of other risk factors. After adjustment, risks for seroconversion increased from 2.99 (95% CI: 1.02, 8.76) for men who reported using stimulants only (1 drug) to 8.45 (95% CI: 2.67, 26.71) for men who reported using all 3 sex-drugs. The use of any of the 7 possible sex-drug combinations accounted for 63% of the nine-year HIV seroincidence in the Multicenter AIDS Cohort Study (MACS). When contributions of increased URASP and combination drug use were analyzed together, the total attributable risk for HIV seroconversion was 74%, with 41% attributable to URASP alone and a residual of 33% due to other direct or indirect effects of sex-drug use. CONCLUSIONS: Use of poppers, stimulants and EDDs increased risk for HIV seroconversion significantly in this cohort. These data reinforce the importance of implementing interventions that target drug-reduction as part of comprehensive and efficacious HIV prevention strategies.